Dexmedetomidine as an adjunct to propofol in patients undergoing elective endoscopic retrograde cholangio-pancreaticography - A double-blind randomized controlled study - T Raghavendra Babu; M R Anil Kumar; N R Anup; Sarika M Shetty (Wolters Kluwer Medknow Publications, 2024)
Background: Propofol is the drug of choice for procedural sedation. The addition of α2 agonist dexmedetomidine may improve the safety profile of the procedure by providing stable hemodynamics, better sedation quality, and decreasing the side effects of each drug during elective endoscopic retrograde cholangio-pancreaticography (ERCP). Materials and Methods: Eighty patients aged between 18 and 60 years were distributed randomly into two groups. The dexmedetomidine + propofol group (group DP) received an injection of dexmedetomidine at the dose of 1 mcg/kg in 100 mLsaline, and the propofol group (group P) received plain 100 mL normal saline over 10 min. Subsequently, both groups received a bolus dose of injection propofol 1 mg/kg as sedation, and a modified observer's assessment of alertness/sedation score (MOASS) score was assessed, followed by infusion at the rate of 50 mcg/kg/min during the procedure. A rescue bolus dose (20 mg) of propofol was administered when the patient showed signs of inadequate sedation or analgesia in both groups. Cardiovascular and respiratory parameters were recorded every 10 min throughout the procedure. Post-procedure modified Aldrete score was evaluated for 30 min, and the endoscopist's score was noted at the end of the procedure. Results: There was a significant difference (P = 0.001) in the additional number of rescue doses of propofol administered in group DP (3.47 ± 0.77) as compared to group P (8.78 ± 1.11). The total dose of propofol was lower in group DP (316.59 ± 43.29 mg) than in group P (443 ± 41.1 mg) with P value = 0.001. Statistically significant differences in the hemodynamic values were observed in group DP during infusion (P value < 0.05) of dexmedetomidine and throughout the procedure (P < 0.05) when compared with group P. Endoscopists graded the satisfaction score as very high (3.477 ± 0.77) in group DP. Conclusion: The addition of dexmedetomidine to propofol during ERCP provided better and safer sedation.